The diagnosis of delirium in 80 emergency unit patients - AFONSO CARLOS NEVES; RICARDO DE CASTRO CINTRA SESSO; HENRIQUE BALLALAI FERRAZ; SÍLVIO FRANCISCO; JOÃO BAPTISTA DOS REIS-FILHO (Arquivos de Neuro-Psiquiatria)
We evaluated the initial and final diagnosis of 80 patients with delirium arriving at the emergence unit of a university hospital in a large Brazilian city over a period of 30 months up to December 1991. The diagnosis was based on the DSM-IIIR criteria. Patients with a known history of head trauma or epileptic seizure and patients younger than 13 years were excluded. Only patients with a disease of up to 7 days were included.The patients were subdivided into four etiologic groups: vascular; associated with the use of alcohol; infectious-parasitic; miscellaneous.The results showed a rate of correct diagnosis ranging from 65 to 80% with the use of kappa test (standard good to excelent). Sensitivity, specificity, positive predictive and negative predictive values had results showing different conditions for initial diagnosis in each group. This study can help the initial diagnosis of delirium and the choice for diagnostic testing.